Beyond Macroeconomic Stability : The Quest for Industrialization in Uganda - Selassie, Abebe Aemro (IMF Working Papers; Working Paper, 2008)
Uganda has registered one of the most impressive economic turnarounds of recent decades. The amelioration of conflict and wide ranging economic reforms kick-started rapid economic growth that has now been sustained for some 20 years. But there is a strong sense in policy making circles that despite macroeconomic stability and reasonably well functioning markets, economic growth has not translated into significant structural transformation. This paper considers (i) Uganda's record of economic transformation relative to the high growth Asian countries and (ii) the contending explanations as to why more transformation and higher growth has proved elusive.